Long-Read Sequencing Revealed Extragenic and Intragenic Duplications of Exons 56–61 in DMD in an Asymptomatic Male and a DMD Patient - Bai, Ying; Liu, Ju; Xu, Jinghan; Sun, Yue; Li, Jingjing; Gao, Yong; Liu, Lina; Jia, Cangcang; Kong, Xiangdong; Wang, Li (Frontiers in Genetics, 2022)
Expanded carrier screening (ECS) has become an increasingly common technique to assess the genetic risks of individuals in the prenatal or preconception period. Unexpected variants unrelated to referral are increasingly detected in asymptomatic individuals through ECS. In this study, we reported an asymptomatic male with duplication of exons 56–61 in DMD gene through ECS using whole exome sequencing (WES), which was also detected in a male patient diagnosed with typical Duchenne Muscular Dystrophy (DMD). Breakpoint analysis was then performed to explore the potential mechanisms of phenotypic differences using long-read sequencing (LRS), PacBio single molecule real-time (PacBio SMRT) target sequencing and Sanger sequencing. Complex structural variations (SVs) on chromosome X were identified in the asymptomatic male, which revealed that the duplication occurred outside the DMD gene, while the duplication in the patient with DMD was a tandem repeat. The phenotypic differences between the two males could be explained by the different breakpoint junctions. To the best of our knowledge, this is the first report of a breakpoint analysis of DMD duplication in two males with different phenotypes. Breakpoint analysis is necessary when the clinical phenotypes are inconsistent with genotypes, which applies to prenatal testing.